Իրան-Հնդկաստան դիվանագիտական հարաբերությունների սկզբնավորման շուրջ - Գևորգյան, Աշխեն («Զանգակ - 97»)
The aim of the work is to present the course of Iran-India relations in 1950-1979. To show the circumstances and problems that hindered the establishment of relations between the two countries. We have also presented the processes due to which Iran and India were able to strengthen their relations by cooperating in commercial, economic and other fields. Observing the rapid development of Iran-India relations, we notice that the two countries had studied each other's capabilities in depth and had a good idea of the positive impact of cooperation both in the country's internal and external fields. Despite the fact that there was a certain pause in the relations between the two countries after the Islamic revolution in Iran in 1979, later Iran and India maintained high-level relations, actively cooperating in almost all fields.
Keywords: Միջազգային հարաբերություններ